Developing silicate-cored extruded earth block a key to Philippine yahkchal - Hela, Neil Karlo C. (2019)
This study was conducted to promote the use of rice husk as silicate for the extruded earth blocks and specifically aims to reduce the thermal conductance, improve the thermal resistance of the building, regulate the thermal transmittance of the exterior heat towards the interior, and lastly to determine its thermal performance in comparison to other conventional materials such as concrete hollow blocks. The study is mainly focused on developing and experimenting on the samples. The earth block is first formed, extruded and cut before letting it dry. After it has been dried, it is then loaded in a kiln and fired for several hours. After letting it cool, the final product is then subjected to a series of test to determine its thermal performance. The experimental part involves Temperature Test where the samples are placed under the sun and the temperature of the samples being tested is taken on a certain time. It also involves Heat Transfer Test which subjects the samples in acontinuous flame until the other side of the sample reaches a certain temperature. The Axial Heat Flow Method was also conducted on the samples. This involves a heat source with a steady power heating the samples and recording the temperature at specific points on the sample. The results show that Rice Hull Ash is a more effective core for the extruded earth. It has the lowest thermal conductance and thermal transmittance, and the highest thermal resistance among the samples. The silicate-cored extruded earth block performed well against the concrete hollow block, a conventional building material.The final product is used in designing a low-cost, medium density residentialarea. The final product is incorporated in the wall system of the buildings. The subdivision contains, an activity hall, commercial strip, production shed, and a material recovery facility.